Impact of Pandemic on Zakat Receiving and Distribution at Baznas Kabupaten Karawang - Isro'iyatul Mubarokah; Fety Nurlia Muzayanah (EAJ (Economic and Accounting Journal), 2021)
The impact of the pandemic has resulted in many people losing their jobs. This causes the potential for muzakki to decrease and mustahik to increase. This paper will examine how zakat is received and distributed before and after the pandemic. The method used in this research is descriptive qualitative. The data used in this study are primary and secondary data. The results showed that there was a decrease in both the collection and receipt of zakat after the Covid-19 pandemic. BAZNAS Karawang Regency needs to make various efforts to improve the collection and distribution of zakat in Karawang Regency again.